DETERMINAN MINAT MAHASISWA AKUNTANSI MENGIKUTI PENDIDIKAN PROFESI AKUNTANSI - Sparta Sparta; Satria Purwantoro Purwantoro (Universitas Trilogi, 2026)
This study is motivated by the relatively low interest of accounting students in pursuing Professional Accounting Education (PPAk), despite the growing demand for professional accountants. This study aims to examine the effect of quality motivation, career motivation, and economic motivation on accounting students’ interest in pursuing PPAk. A quantitative survey was conducted involving 116 active accounting students at STIE Indonesia Banking School from the 2020–2023 cohorts. Data were collected using a Likert-scale questionnaire and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS 4.0. The results indicate that quality motivation has a positive and significant effect on students’ interest in pursuing PPAk. Career motivation also has a positive and significant effect and represents the strongest determinant in the model. In contrast, economic motivation does not significantly affect students’ interest in pursuing PPAk. These findings suggest that students’ intention to enroll in PPAk is driven more by competence development and career orientation than by direct financial considerations. The study provides practical implications for higher education institutions and PPAk providers to strengthen career socialization, competency-based learning, and professional accounting mentoring.Keywords: Career motivation; Economic motivation; Professional Accounting Education; Quality motivation; Student interest